Good & evil actions : a journey through Saint Thomas Aquinas - Jensen, Steven J., 1964- (Washington, District of Columbia : Catholic University of America Press, 2010)
"In Good and Evil Actions, Steven J. Jensen tackles the Thomistic debate surrounding the inherent good and evil of human actions. With exceptional clarity, he identifies the essential issues, resolves conflicting views, and reveals the truth as conveyed by Aquinas."--BOOK JACKET.
Human actions -- Intention -- Exterior actions -- Love of others -- Difficulties -- Teleology -- Moral species.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Thomas, -- Aquinas, Saint, -- 1225?-1274.; Good and evil; Good and evil -- History of doctrines -- Middle Ages, 600-1500.; Thomas, -- Aquinas, -- 1225?-1274.; Goed en kwaad; Handelen; PHILOSOPHY / Ethics & Moral Philosophy; BIOGRAPHY & AUTOBIOGRAPHY / General; Electronic books